Peran Guru Dalam Menangani Keterlambatan Berbicara Pada Anak Usia 5-6 Tahun: Studi Kasus Di RA Bunda Az-Zahra - Nandasary, Yunira; Akbari, Akbari (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE ROLE OF TEACHERS IN HANDLING SPEAKING DELAYS IN CHILDREN AGED 5-6 YEARS: A CASE STUDY AT RA BUNDA AZ-ZAHRA This study aims to describe the role of teachers in addressing speech delay among children aged 5–6 years at RA Bunda Az-Zahra using a descriptive qualitative approach. Early childhood is a critical developmental period, particularly in language acquisition, which forms the foundation for communication, social interaction, and cognitive growth. Within this context, teachers play an essential role in providing appropriate stimulation to support language development, especially for children who experience delays in speech. Data were collected through classroom observations, interviews with two homeroom teachers, and documentation of the progress of HA, the primary subject of this study. The findings reveal that teachers perform five key roles: facilitator, motivator, guide, mediator, and evaluator. Teachers utilize simple classroom media such as pictures, thematic books, songs, and learning tools to stimulate verbal expression. Praise, repeated instructions, and verbal modeling serve as primary strategies in motivating and guiding the child. Teachers also mediate social interactions and conduct observational assessments to monitor language progress. Although the school does not provide specialized facilities or formal intervention programs, the teachers’ adaptive and consistent strategies contribute positively to improving the child's speaking ability. This study highlights the importance of teachers’ involvement in early intervention for children with speech delay through communicative, supportive, and continuous instructional approaches.